A pH/MMP-9 smart dual-responsive liposome GBE@LP co-delivers and controls the release of GB1107/BMS1166/Enzalutamide for liver cancer immunotherapy - Shijia Lu; Chenxiao Zhang; Huiru Wu; Junjie Wang; Jinglong Wang; Limei Zhao; Tianyang Ren; Guofei Li (Materials Today Bio)
Liver cancer is one of the malignant tumors with high morbidity and mortality worldwide and lacks effective clinical treatments. CD8+ T cell-based immunotherapy is the most promising option for the treatment of liver cancer, but its application is severely limited by low infiltration and functional exhaustion of CD8+ T cells in liver cancer tissues. To overcome this problem, in this study, pH/matrix metalloproteinase-9 (MMP-9) dual-responsive liposomes were constructed and co-loaded with a galectin-3 (Gal-3) inhibitor, GB1107, a programmed death receptor 1 (PD-1) inhibitor, BMS1166, and an androgen receptor (AR) antagonist, enzalutamide, for immunotherapy studies in liver cancer. Specifically, the co-loaded liposomes (GBE@LP) were produced with a one-two punch targeting antitumor immunity. First, GBE@LP exhibited prolonged circulation in the blood and accumulated in liver cancer tissues through the enhanced permeability and retention effect due to the presence of surface polyethylene glycol. After entering liver cancer tissues, GBE@LP responded to the low pH and overexpression of MMP-9 in the microenvironment to promote the release of GB1107, BMS1166, and enzalutamide, thus, realizing the intelligent release of drugs targeting liver cancer. Upon reaching liver tumor tissues, GB1107 can inhibit overexpressed Gal-3 to transform liver cancer from a “cold” to a “hot” tumor and enable deep penetration by CD8+ T cells. In addition, BMS1166 and enzalutamide inhibit PD-1 and AR in CD8+ T cells, reversing CD8+ T cell exhaustion and enhancing their killing activity. In vivo and in vitro experiments confirmed the significant antitumor effects of GBE@LP in liver cancer. These results indicate that our strategy is expected to reverse the “cold” tumor and immune exhaustion state of liver cancer, which not only improves therapeutic efficacy, but also provides a new paradigm for the exploration of liver cancer immunotherapy.